Global Health and Visa Policy Reform to Address Dangers of Hajj during Summer Seasons - Aleeban, Mohanad; Mackey, Tim K. (Frontiers in Public Health, 2016)
Every year on the 12th month of the Islamic calendar, 2-3 million Muslims from over 160 countries migrate to Holy sites in Saudi Arabia to perform the Hajj, representing one of the largest mass gathering events worldwide. Yet, the Hajj poses several challenges to global health and public safety, including the unique health risks posed by seasonal variability when Hajj occurs during summer months. Specifically, pilgrims taking the journey to Mecca are at higher risk for heat illnesses, heat-related injuries and exhaustion, and stampedes, when summer temperatures can reach up to 48.7°C. In response, we propose that the Saudi government, in coordination with the Organization of Islamic Cooperation and the World Health Organization, explore the establishment of an expert committee, create and use a predictive risk modeling tool, and establish a dynamic quota on Hajj visas to limit potential heat exposure for high-risk populations when the Hajj falls on seasons associated with extreme weather exposure. As climate change is projected to lead to future increases in temperatures in the region, this form of dynamic and evidence-based policymaking is needed to ensure human health and safety for generations of Hajj pilgrims to come.